Improved Science Learning Outcomes through Technology Assisted Experimentation: Peningkatan Hasil Belajar IPAS melalui Eksperimen Berbantuan Teknologi - Sahra, Aulia Az.; Rahman, Abdul; Pendit, Sinta Satria Dewi; Azizah, Azizah; Rini, Eva Setya (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Elementary science learning requires active and contextual strategies to develop conceptual understanding and scientific skills. Specific Background: Classroom practice remains teacher-centered, limiting student engagement and resulting in low achievement levels, as indicated by pretest scores below the expected standard. Knowledge Gap: Limited integration of simple experimental activities with accessible digital support restricts opportunities for experiential and repeatable learning processes. Aims: This study aims to examine the role of technology-assisted simple experimental learning in improving science learning outcomes. Results: Using a pre-experimental design with one group pretest-posttest involving 16 students, the findings show an increase in mean scores from 49.22 to 80.36, supported by paired sample t-test results (t = -7.347; p = 0.001), indicating a statistically significant difference. Novelty: The integration of QR Code technology as procedural scaffolding enables repeated access to experimental steps, supporting independent and flexible learning. Implications: The findings suggest that combining simple experiments with accessible digital tools can support active learning, improve conceptual understanding, and offer a practical instructional alternative in resource-limited contexts, while highlighting the need for broader designs to strengthen generalizability. Highlights• Mean score progression demonstrates substantial academic improvement after intervention• Statistical testing confirms significant difference between initial and final assessment• Digital scaffolding supports procedural clarity and autonomous engagement KeywordsExperimental Learning; Technology Integration; Science Education; Learning Outcomes; QR Code